2016
DOI: 10.18632/oncotarget.12061
|View full text |Cite
|
Sign up to set email alerts
|

The other face of miR-17-92a cluster, exhibiting tumor suppressor effects in prostate cancer

Abstract: miR-17-92a cluster miRNAs are transcribed from a polycistronic transcription unit C13orf25 that generates six mature miRNAs, miR-17, miR-18a, miR-19a, miR-19b, miR-20a and miR-92a that are overexpressed in lung and colon cancers. Here we show that the expression of miR-17-92a miRNAs are reduced in cancerous prostate tissues compared to uninvolved areas and also in aggressive prostate cancer cells. Restoration of expression of all members of miR-17-92a cluster showed, decreased expression of cell cycle regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 66 publications
5
40
0
1
Order By: Relevance
“…MiR-19b has been implicated as a potential oncomiR in many cancers (Olive et al, 2009, Jin et al, 2013, and it has been assigned potential cancer-promoting functions in breast cancer via negative regulation of tumour suppressor genes such as PTEN (Li et al, 2014), PTPRG (Liu et al, 2016) and BRCA2 (Mogilyansky et al, 2016). In contrast, our data support a tumour suppressor role for miR-19b in breast epithelial cells, in accordance with some data in prostate cancer (Ottman et al, 2016) and hepatocellular carcinoma (Hung et al, 2015). HuR has also been defined as an oncogene, with higher expression associated with poor survival in breast and other cancers (Zhu et al, 2013, Denkert et al, 2004, and it is the focus of ongoing work to develop novel targeted therapeutics (Huang et al, 2016, Muralidharan et al, 2017, Wu et al, 2015.…”
Section: Discussionsupporting
confidence: 91%
“…MiR-19b has been implicated as a potential oncomiR in many cancers (Olive et al, 2009, Jin et al, 2013, and it has been assigned potential cancer-promoting functions in breast cancer via negative regulation of tumour suppressor genes such as PTEN (Li et al, 2014), PTPRG (Liu et al, 2016) and BRCA2 (Mogilyansky et al, 2016). In contrast, our data support a tumour suppressor role for miR-19b in breast epithelial cells, in accordance with some data in prostate cancer (Ottman et al, 2016) and hepatocellular carcinoma (Hung et al, 2015). HuR has also been defined as an oncogene, with higher expression associated with poor survival in breast and other cancers (Zhu et al, 2013, Denkert et al, 2004, and it is the focus of ongoing work to develop novel targeted therapeutics (Huang et al, 2016, Muralidharan et al, 2017, Wu et al, 2015.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are very similar to a study of Ottman et al, in which they showed downregulation and anti-proliferative properties of miR-20a in prostate cancer cells [25] . On the other hand, several studies demonstrated an upregulated expression of oncogenic miR-20a in other malignancies, highlighting miR-20a's heterogeneity in expression and functionality in a tissue and cell type-specific manner [26] .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, changes in the level of miR-19b-3p expression were analyzed, which serve a significant role in the development of a number of cancer types (39,40), as well as in metastasis (41) and tumor response to drug therapy (42). A miRNA panel including miR-19b-3p in peripheral plasma was identified and proposed as a biomarker in diagnosis of adenocarcinoma lung cancer as reported by Zhou et al (43).…”
Section: Discussionmentioning
confidence: 99%